Electrospun PLGA membrane incorporated with andrographolide-loaded mesoporous silica nanoparticles for sustained antibacterial wound dressing. (14th November 2018) - Jia, Yuhang; Zhang, Hongbo; Yang, Shengbing; Xi, Zhenhao; Tang, Tingting; Yin, Ruixue; Zhang, Wenjun
Aim: To assess the wound-healing ability of poly(lactic- co -glycolic acid) (PLGA) nanofibrous wound dressing incorporated with andrographolide (Andro)-loaded mesoporous silica nanoparticles (MSNs).Materials & methods: PLGA/Andro-MSNs nanofibrous membrane wound dressings were produced by electrospinning. The effects of MSNs on the hydrophilicity, degradation and mechanical strength of membranes were evaluated. The cumulative release of Andro in vitro was obtained. Cell culture and in vivo tests on infectious models were carried out.Results: The PLGA/Andro-MSNs membrane showed a sustained release of Andro. The incorporation of MSNs into PLGA improved the hydrophilicity of the nanofibrous membranes. Cell culture and in vivo tests showed that PLGA/Andro-MSNs membrane can promote epidermal cell adhesion and reduce inflammation process.Conclusion: PLGA/Andro-MSNs nanofibrous membrane exhibited an efficient wound-healing ability.